Exploring the metabolic-immune score in advanced NSCLC treated with immunotherapy - Beliz Bahar Karaoğlan; Ecenur Dursun; İrem Mesci; Mine Soylu Araz; Elif Berna Köksoy (Scientific Reports)
Abstract Identifying reliable prognostic markers in patients with advanced non-small cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs) is critical for clinical decision-making. This study introduces the Metabolic and Immune Score (MIS), a novel scoring system combining metabolic and inflammatory markers. A retrospective analysis was conducted on 56 patients with advanced NSCLC treated with ICIs between January 2018 and January 2024. Baseline metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were calculated using 18F-FDG PET-CT imaging. Systemic inflammatory status was assessed using the Lung Immune Prognostic Index (LIPI). Median values for MTV and TLG were used as cut-off points. Primary outcomes were progression-free survival (PFS) and overall survival (OS). Patients with a LIPI score of 0 demonstrated significantly longer PFS (25.1 vs. 4.1 months, P < 0.001). High TLG levels (> 250.20) were also associated with shorter PFS (4.0 vs. 12.5 months, P = 0.021). On baseline PET-CT, median MTV and TLG were determined as 57.29 cm³ and 250.20, respectively. The MIS, derived from the combination of these two parameters, stratified patients into good, intermediate, and poor prognostic groups. Significant differences in PFS were observed among MIS groups (25.1, 6.3, and 1.5 months; P < 0.001), whereas median OS was not yet reached in the favorable group, and was 13.1 and 5.0 months in the intermediate and poor groups, respectively (P = 0.029). The MIS combines LIPI and TLG, providing a useful tool for predicting outcomes in advanced NSCLC patients treated with immunotherapy. Further validation in larger cohorts is warranted.